Legal regulation of the informational and analytical activity of the State aviation service of Ukraine - Горбатюк, Яна Вадимівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
In the article the author defines the concept and system of the legal regulation of informal and analytical activity of the State aviation service of Ukraine, indicates deficiencies of the legal regulation of this activity